Analisis Proses Pengelolaan Arsip Dinamis Inaktif pada Unit Kearsipan Kementerian CX - Sundari, Anissa Aprilia; Lawanda, Ike Iswary (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2023)
Management of inactive records must be carried out to maintain their value and prevent them from becoming messy. Messy records are still found in the archive storage of the Ministry of CX's Record Center. The processing unit sends these records in the form of boxes and sacks without a file list attached. Archives have a very important role as a source of information for an organization. This study aims to explain the management of inactive dynamic archives at the Archives Unit of the Ministry of CX in terms of procedures, human resources and also facilities and infrastructure as a form of archivist compliance with the rules. The research method used is the case study method with a qualitative approach. The data collection technique used for this research is an interview with eight informants who were archivists at the Ministry of CX. The results of this study indicate that, in handling inactive records, there are still many messy records caused by the knowledge and awareness of the processors in interpreting the records in the organization. This affects the compliance of archivists in the Processing Unit to manage their records properly, even though there are procedures and policies in place, problems are still caused in the original order at the Archives Unit. Supporting facilities and infrastructure were converted and rooms did not meet standards. As a result, archivists in the Archives Unit must re-manage it so that it is in accordance with the original order of the archives in the Archives Unit.